New Representation Method For Integers And Its Application On Elliptic Curve Cryptography - Eghdamian, Arash (2020)
Public-key cryptosystems are broadly used in security protocols such as key agreement, authentication, encryption and others. The two main operations in many public-key algorithms are multiplication and exponentiation of large numbers. The performance and efficiency of these cryptographic primitives are highly reliant on the efficiency of these operations. Improving the efficiency of multiplication and exponentiation by applying a recoding method or using a specific number system which can reduction the Hamming Weight of numbers is very common. This study proposes a new Radix-r representation for integers which is known as Modified Generalized Non-Adjacent Form (MGNAF).